Size premium estimation based on WSE trading data - Karásek, David; Rýdlová, Barbora, 1976-; Sóoky, Jakub; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This master thesis examines the existence and magnitude of a size premium on the Warsaw Stock Exchange. The size premium, commonly used in estimating the cost of equity, assumes that smaller companies generate higher returns than larger ones. Using a practitioner-oriented approach based on equal-weighted quartile portfolios, the thesis analyses excess returns over the risk-free rate between 2000 and 2024. The results show a consistent underperformance of the smallest firms, contrary to expectations. Liquidity was then examined as a possible explanation, but differences were not sufficient to justify the effect. The findings suggest that global size premium estimates may not apply to Poland and highlight the need for local market-specific inputs in valuation.
Vedoucí práce: Barbora Rýdlová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses